Death rates and causes among admitted neonates in Children Welfare Teaching Hospital – Medical city –Baghdad (2000- 2004) - Hameed, Numan N. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: The neonatal deaths account for two-third of all deaths in the first year of life, and 40% of under-five mortality. Extreme prematurity, respiratory distress syndrome , neonatal infections , and congenital malformations are among the common causes of neonatal deaths.Methods: We retrospectively studied 668 neonates who died over 5 years period from first of Jan. 2000 to the end of Dec. 2004 in neonatal care unit of children Welfare Teaching Hospital-medical city, by obtaining data from reviewing their medical records and death certificates.Results: The death rate in neonates admitted to SCBU (special Care baby Unit) during the period of study was (10.7%), male constituted 432 (64.7%) and female 236 (35.3%) with male to female ratio 1.8:1. The major causes of death were congenital malformations (41.6%), neonatal infections (33.4%),and prematurity (10.3%).Conclusions: There was no decline in the neonatal death rate in our hospital especially from sepsis and prematurity and low birth weight. Death due to late onset sepsis was lower than that due to early onset sepsis .There was a significant increase in the death from congenital malformations.